Long-term Developmental Trends of Pediatric Mitochondrial Diseases: The Five Stages of Developmental Decline - Eom, Soyong; Lee, Young-Mock (Frontiers in Neurology, 2017)
Mitochondrial diseases (MDs) are a heterogeneous group of progressive multisystem disorders caused by impaired mitochondrial function. This study aimed to evaluate the clinical course and long-term development of 53 pediatric patients with mitochondrial diseases. Developmental function was evaluated at nine time points (two pre-diagnosis, one at diagnosis, and six post-diagnosis), with the developmental quotient (DQ) from the Korean Infant and Child Development Test (KICDT) assessing a child’s developmental age (rather than chronological age). Additionally, disease-related clinical variables were reviewed, and clinical progress was determined through observation. Subgroup analyses by epilepsy severity, syndromic diagnosis, diffuse brain atrophy, and clinical rating were performed. The pre- and post-diagnosis results were compared by the paired t-test and Bonferroni correction. The pre-diagnostic, diagnostic, and post-diagnostic evaluations were compared using repeated-measures ANOVA. Patients with diffuse brain atrophy at the first pre-diagnostic and second post-diagnostic evaluations showed lower developmental quotients. Compared with patients with a mildly or severely deteriorating clinical course, those with an improving or static clinical course presented higher developmental quotients at the pre-diagnostic and diagnostic evaluations. The age at onset of the first symptom correlated positively with the developmental quotient post-diagnosis. Follow-up revealed consistent patterns of significant developmental deterioration during the lead time to diagnosis, with no significant decline post-diagnosis. The developmental quotient is a feasible predictor and a measure of long-term functional development in children with mitochondrial disease. Early initiation of treatment may minimize developmental regression.